Development of business models in the fourth industrial revolution: Conditions in the context of empirical research on worldwide scope companies located in Poland - Sandra Grabowska; Sebastian Saniuk (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Ubiquitous digitization, changing competitive intensity, and rapid development of new technologies are shaping the new business landscape, creating new opportunities for consumers and businesses. There is a need to create open business models that allow for the introduction of open innovations, rapid reorganization of processes, and flexibility in adapting modern enterprises to dynamically changing market conditions. The achievements and results presented in the article were obtained by conducting a survey using the CAWI method, among 70 purposefully selected companies; the research was carried out in Poland. The impact of Industry 4.0 technology on business models, barriers to the implementation of these technologies, and changes in business models that occurred as a result of this implementation were identified. The article is dedicated to researchers working on business models and business practitioners.
Keywords: 650; business models; digitalization; Fourth Industrial Revolution; Industry 4.0; open business model; open innovation